GAGASAN DIBALIK KECENDERUNGAN PENGGUNAAN BENTUK KOTAK PADA ARSITEKTUR - Purnama Salura; Rivana Chandra; Andreas Yanuar Wibisono (Universitas Katolik Parahyangan, 2011)
We are all familiar with the tagline ”experience the modern box house” or ” the green tropical minimalist housing”. Or how about this story, about a meeting of an operating manager with his client;… after talking about his house project, the client asked ”what do you think is best for my house?’. The operating manager answered ”Well, it depends on you. What kind of style do you like, there is minimalist-style which is very popular these days. It shaped like stacks of boxes. And there is also classical-style, whatever you like”.These are the phenomenon of architectural practice nowadays. It is considered as if the only truth that is shown consistently and continuously. Style has been dominant. Life-style became the great operation tool that gave us the useful sight of information practically and academicly.The architectural data from the objects is collected in order to be compared by the theory of cultural and natural contextuality in architecture. Symbols and characteristic that is attached to the object is used to analyze the connection to the local culture and nature.Both objects that is chosen shows no connection to the earlier local culture that had exist before them. It is influencing the balance between the building and its enviromental nature. This ‘box-shaped architecture’ shows how imbalance the connection among buildings (architecture) and its local culture and nature.Keywords: style, culture, nature, contextual, fit